Kompetensi Perawat Dan Kepuasan Pasien Terhadap Pelayanan Keperawatan di Rawat Jalan: Nurse Competence and Patient Satisfaction with Nursing Services Nursing Services in Outpatient - Imelda Rahmayunia Kartika; Rr. Tutik Sri Hariyati; Nelwati (NERS Jurnal Keperawatan, 2018)
Nurse competence becomes an important part that must be considered in carrying out nursing care for patients, in order to achieve patient satisfaction. Nurses' competencies in conducting assessments, nursing interventions and communication in patients on outpatient care still need to be improved. Outpatient Hospital Dr. Achmad Mochtar Bukittinggi still stated unsatisfied with nurse interactions. The purpose of this study was to determine the relationship between nurse competency and outpatient satisfaction on nursing care. The design of this study uses descriptive correlation with a cross sectional approach. The total sample of 295 outpatients was taken purposively. The instrument used was a modification of the PSNCS (Patient Satisfaction with Nursing Care Scale) and NSNS (Newcastle Satisfacton to Nursing Scale). Data analysis using Spearman Correlation. Patient satisfaction is at the middle level (Mean = 33 in the score 12 - 60), while the mean for nurse competence is 12.39. The results of this study indicate a significant relationship between nurse competence and patient satisfaction (p value = 0,0001) and r value = +0,500, which means showing a directional relationship. The value of the determinant coefficient (r2) is 0.25, which means that nurse competence can explain patient satisfaction by 25%. This shows that the higher the competence possessed by a nurse in outpatient care, the higher the patient's satisfaction in nursing services. It is expected that nurses can improve their competence so that satisfaction and quality of nursing services can be increased.